2003
DOI: 10.1046/j.1460-9592.2003.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid emergence does not explain agitation following sevoflurane anaesthesia in infants and children: a comparison with propofol

Abstract: Although both sevoflurane and propofol allow for rapid emergence from general anaesthesia, only sevoflurane is associated with a high incidence of emergence agitation in infants and young children. Rapid emergence does not fully explain this phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(106 citation statements)
references
References 25 publications
(33 reference statements)
5
97
1
3
Order By: Relevance
“…Thus, we strongly recommend that pain should be anticipated and treated preventively, as early as during surgery itself, and that the proper postoperative analgesia be used after major operations, such as thoracic and abdominal surgeries. 2,15 The incidence of agitation in males was greater than in females. This may be due to the lower pain tolerance in males following surgery, as previous studies have reported that men report more pain and consume more patient-controlled analgesia than women.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we strongly recommend that pain should be anticipated and treated preventively, as early as during surgery itself, and that the proper postoperative analgesia be used after major operations, such as thoracic and abdominal surgeries. 2,15 The incidence of agitation in males was greater than in females. This may be due to the lower pain tolerance in males following surgery, as previous studies have reported that men report more pain and consume more patient-controlled analgesia than women.…”
Section: Discussionmentioning
confidence: 98%
“…The only inhalational agent not associated with emergence delirium is halothane [7] and this is no longer available in the UK. Although both sevoflurane and propofol allow for rapid emergence from general anaesthesia, a comparison of sevoflurane and propofol found that only sevoflurane was associated with a high incidence of emergence delirium in infants and young children, so rapid emergence itself does not explain this phenomenon [8].…”
Section: Editorialmentioning
confidence: 99%
“…Ancak, sevofluran ve propofol anestezisinin karşılaştı-rıldığı bir başka çalışmada, propofol anestezisi alan çocuklarda, derlenme daha hızlı olmasına karşın, postoperatif ajitasyon insidansı sevofluran grubunda belirgin olarak daha yüksek bulunmuştur. (17,18) Mayer ve ark. 'nın (19) sevofluran indüksiyonu sonrasında anestezi idamesinde desfluran ve sevofluranı karşılaştırdığı bir çalışmada da, desfluran alan grupta derlenmenin daha hızlı olduğu, postoperatif ajitasyonunun ise sevofluran grubunda anlamlı olarak yüksek olduğu gösterilmiştir.…”
Section: Gereç Ve Yöntemunclassified